2003
DOI: 10.1177/000348940311201101
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the Vocal Fold Using Autologous Mesenchymal Stem Cells

Abstract: The aim of this study was to regenerate the injured vocal fold by means of selective cultured autologous mesenchymal stem cells (MSCs). Eight adult beagle dogs were used for this experiment. Selective incubation of MSCs from bone marrow was done. These MSCs were submitted to 3-dimensional incubation in 1% hydrochloric acid atelocollagen. Three-dimensional incubated MSCs were injected into the left vocal fold, and atelocollagen only was injected into the right vocal fold of the same dog as a control. Four days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(37 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Histologic and rheologic assays were performed three months post-injury and revealed reduced collagen abundance, reduced lamina propria thickness, and improved dynamic viscosity compared to saline-treated controls. These promising findings align with earlier work published by this research group and others [25, 26]. …”
Section: Treatmentsupporting
confidence: 93%
“…Histologic and rheologic assays were performed three months post-injury and revealed reduced collagen abundance, reduced lamina propria thickness, and improved dynamic viscosity compared to saline-treated controls. These promising findings align with earlier work published by this research group and others [25, 26]. …”
Section: Treatmentsupporting
confidence: 93%
“…[54,56,92] Kanemaru et al was the first to report the therapeutic benefit of injecting autologous MSCs encapsulated in 1% hydrochloric acid atelocollagen to facilitate the regeneration of injured canine vocal folds. [93] The observed in vivo cell proliferation within the atelocollagen scaffold indicated that atelocollagen is suitable for vocal fold tissue engineering. Kishimoto et al continued to investigate the restorative effects of a scaffold on vocal fold scarring and sulcus vocalis by implanting atelocollagen sheet into patients with post-cordectomy scar or sulcus vocalis.…”
Section: Biomaterials In Development/researchmentioning
confidence: 99%
“…45 Mesenchymal stem cells have already been shown to have useful properties in the regeneration of damaged vocal folds. 46 Although it is unknown if the preepiglottic space fat donated to CTAP contains a population of mesenchymal stem cells, certainly the notion of presenting a damaged vocal fold with a fresh population of stem cells is attractive.…”
Section: Discussionmentioning
confidence: 99%